Production of linearly polarized photon beam at MAX-lab - Ganenko, V.B.; Fissum, K.; Hansen, K.; Isaksson, L.; Livingston, K.; Lundin, M.; Morokhovskii, V.; Nilsson, B.; Pugachov, D.; Schroder, B.; Vashchenko, G. (Вопросы атомной науки и техники, 2009)
Spectra of coherent bremsstrahlung from the diamond crystal in the laboratory MAX-lab on the accelerator MAX-I are measured at the energy of the electronic beam 144 MeV . First in the laboratory MAX-lab a source of the polarized photon radiation was created. Photon spectra were compared with theoretical calculations, that allow to estimate a magnitude of photon polarization, which is su±cient, for performing the nuclear experiments in the intermediate energy range.